PENGARUH EFISIENSI OPERASIONAL DAN LIKUIDITAS DENGAN RISIKO KREDIT SEBAGAI VARIABEL MODERASI PADA PROFITABILITAS BPR - Alessandro Simanihuruk; Agung Dharmawan Buchdadi; M. Edo Suryawan Siregar (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2024)
This study aims to examine the effect of operational efficiency and liquidity with credit risk as a moderating variable on BPR profitability in West Java Province for the period 2020-2022. The independent variables in this study are operational efficiency proxy BOPO and liquidity proxy Loan to Deposits Ratio (LDR). The dependent variable in this study is profitability proxy Return on Assets (ROA) and moderating variable credit risk proxy Non-Performing Loan (NPL). The number of BPR samples used was 190 BPRs with an observation time of three years so that there were 570 total observations to analyze. The sampling technique used purposive sampling method. The research method used is quantitative with data sources in the form of secondary data. The data analysis method uses panel data regression analysis with Stata version 17. The results of this study indicate that operational efficiency has a negative and significant effect on profitability. Liquidity has no significant effect on profitability. Credit risk is not able to moderate the effect of operational efficiency on profitability. Credit risk is able to moderate the effect of liquidity on profitability